A one-pot route to thioamides discovered by gas-phase studies: palladium-mediated CO2 extrusion followed by insertion of isothiocyanates. Issue 27 (20th March 2017) - Noor, Asif; Li, Jiawei; Khairallah, George N.; Li, Zhen; Ghari, Hossein; Canty, Allan J.; Ariafard, Alireza; Donnelly, Paul S.; O'Hair, Richard A. J.
Abstract : A palladium mediated synthesis of thioamides from aromatic carboxylic acids and substituted isothiocyanates was discovered by gas-phase experiments and theoretical studies. Abstract : A new palladium mediated "one pot" synthesis of thioamides from aromatic carboxylic acids (ArCO2 H + RNCS → ArC(S)NHR + CO2 ) was discovered by gas-phase experiments and theoretical studies. Palladium-mediated decarboxylation of aromatic carboxylic acids followed by addition of substituted isothiocyanates leads to the corresponding thioamide derivatives.